Xây dựng chính sách bổ sung tài liệu truyền thống tại Thư viện Đại học Hà Nội - Nguyễn, Thị Ngà (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Briefs acquisition of collection at Hanoi University Library (HUL) presently; studies and investigates information users, information need, the state of  the art of acquisition work, composition of  traditional collection, available at HUL; suggests formulation of an acquisition policy for this collection and sets forth some recommendations on developing this policy in practical activity of the University.